Diagnosis And In Vitro Control Of Tomato Leaf Spot Caused By Alternaria alternata In Sulaimani Governorate - Ismael, Jalal Hama salih; Omer, Shallaw Adulrahman (Sulaimani Journal for Pure and Applied Sciences, 2018)
Tomato leaf spot and stem canker is a serious disease in Sulaimani Governorate, and causes significant losses in tomato plant, this study carried out at two different locations well-known for tomato production belong to Sulaimani governorate namely; Bainjan located at Bazian district and Kanimanga at Penjween district for this purpose 3 fields at each location randomly taken to study the incidence, severity of the disease, identification the isolates and using 4 different plant extracts namely, (Hypericum triquetrifolium L, Punica granatum L, Allium sativum L and Thymus vulgaris L) for their antifungal activities against A. alternate. The results detected that the highest value of the disease incidences of Alternaria leaf spot of tomato in the two locations were 74.65, 73.19% in Bainjan and Kanimanga respectively, and the maximum disease severities were recorded 78.06 and 67.70% in Kanimanga and Bainjan fields respectively. The data from this fungus, and its isolates indicated that there were two different isolates, each isolate has specific morphological characteristics in their mycelial growth and also different in conidia measurement and their beaks and the number of cells in each conidium. The mean length and width of the Ka isolate conidia were 31.93, 12.36 μm and the mean of beak was 6.52, 4.15 μm for length and width respectively while the mean of Ba isolates was reached 27.68, 9.84 μm for length and width respectively, the mean of conidia beaks was 4.04, 9.84 μm for width and length respectively. Regards to the number of cell, transverse and longitudinal septa Ka for another time recorded superior against Ba isolate. P. granatum extract was revealed the highest mycelial growth inhibition (MGI 100%) for both isolates when used at 80000 µg ml-1, and the next was H. triquetrifolium also recorded maximum (MGI 100%) for Ba isolate and (93.08%) for Ka isolate, when used at 8%. Aquatic extracts of A. sativum significantly inhibited the fungus growth (89.44%), (83.02%) for Ka and Ba isolates respectively at 30%. T. vulgaris comes next in fungus inhibition efficacy beyond A. sativum and recorded (80.58, 78.11%) for Ka and Ba isolates respectively at 30%, 50 ppm of Salicylic acid and Tabsin-Top70 proved minimum mycelial inhibition rate and recorded (23.02 and 45.11%) for Ba, and (41.14 and 22.38%) for Ka isolate at the same concentration. Meanwhile, the MGI reached to 100%when salicylic acid used at 400ppm for both isolates. The MGI were 84.64 and 89.11% when used Tabsin-Top70 at 600ppm for Ka and Ba isolates respectively.
Keywords: Tomato leaf spot; Alternaria alternata; Plant extracts; Salicylic acid,TabsinTop70